Comparative analysis of library services of five 2008 most outstanding libraries of Metro Manila - Pobre, Jacinto Victor C. (2011)
The purpose of the public library is to provide access to books and other materials containing information that would cater to the needs of the population, helping them in the extension of their knowledge and experience. This study conducted a comparative analysis of the different services provided by the top five city libraries from Marikina, Pasig, Quezon City, Manila and Makati, based on four out of seven criteria used in the 2008 Search for Most Outstanding City Libraries of Metro Manila, namely services, programs, access, and physical facilities.